Estudio del silogismo indiciario, como sustento jurídico necesario para aplicar la prisión preventiva. - Freire Yancha, Anthoni Sebastián (2023)
The objective of this investigation is to analyze indicative syllogism as support to apply to preventive detention, which refers to the analysis of certain and known indications, facts, data or circumstances from which it emerges, through logical reasoning with which it is corroborates the existence of the commission of a crime, in this way the indicative syllogism in the application of preventive detention is of great help, since it allows identifying the elements of conviction that are obtained to determine that it is necessary to apply this precautionary measure and ensure the appearance of the defendant until the end of the final trial. The research carried out on the legal and doctrinal analysis of the indicative syllogism against the application of preventive detention in Ecuadorian legislation is developed under a mixed approach where the qualitative and quantitative method is used, which allows logical conclusions and relevant information on the subject to be obtained. of study, the interview technique and the survey are applied to legal professionals with a high legal knowledge in the area of criminal law, as a relevant result of the investigation it is determined that the indicative syllogism is not applied in the criminal justice system and prevents the precautionary measure of preventive detention from being applied in accordance with its purpose and requirements that are established in the Comprehensive Organic Criminal Code. Keywords: Indicative syllogism, Pretrial detention, Exceptionality, Ultima ratio, Legality.